Oral Presentations 1981
DOI: 10.1055/s-0038-1652178
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Smooth Muscle Cell In Culture

Abstract: When smooth muscle from the aortic media of adult pigs, monkeys and rabbits are dispersed into single cells and seeded into primary culture they are in the contractile phenotype and do not undergo cell division when challenged with 5 or 10% whole blood serum. However, after 6-8 days the isolated cells undergo a spontaneous change in phenotype to a synthetic state whereby their contractility is lost and they become responsive to serum mitogens. This change in function is accompanied by distinct morphological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Taken together, these data show that inhibition of rat VSMC proliferation by HMBA is correlated with retention of SM-I and SM-2 in primary cells and with re-expression of these proteins in passaged cells of altered morphology. This correlation between smooth-muscle-specific MHC and proliferation is consistent with the view that de-differentiation is an essential precursor to proliferation [9]. However, other work has shown that heparin causes retention of smooth-muscle-specific MHCs in primary rat VSMCs, but does not prevent the eventual proliferation of the cells, although the length of the cell cycle is increased (D. J. Grainger, C. M. Witchell, J.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Taken together, these data show that inhibition of rat VSMC proliferation by HMBA is correlated with retention of SM-I and SM-2 in primary cells and with re-expression of these proteins in passaged cells of altered morphology. This correlation between smooth-muscle-specific MHC and proliferation is consistent with the view that de-differentiation is an essential precursor to proliferation [9]. However, other work has shown that heparin causes retention of smooth-muscle-specific MHCs in primary rat VSMCs, but does not prevent the eventual proliferation of the cells, although the length of the cell cycle is increased (D. J. Grainger, C. M. Witchell, J.…”
Section: Resultssupporting
confidence: 85%
“…When arterial VSMCs are dispersed into cell culture, they begin to lose smooth-muscle-specific isoforms of MHC and actin and accumulate their non-muscle equivalents before proliferating [5,8]. VSMCs in the de-differentiated state in vitro resemble the cells found in atheromatous plaques [3], and it has been proposed that de-differentiation is an essential precursor to proliferation [9]. If this hypothesis is correct, the de-differentiation process offers a potential target for the selective inhibition of VSMC proliferation, since a variety of other types of cells proliferate without apparently de-differentiating.…”
Section: Introductionmentioning
confidence: 99%
“…All experiments were conducted when cell cultures were at the third or fourth passage Cells were seeded at approximately 2 × 10 4 cells per dish (60 mm) containing 4 mL fresh medium. Cells were identified as vascular SMCs by their hill‐and‐valley configuration at confluence and positive fluorescence staining for smooth muscle actin and myosin . Trypan blue (Sigma) was added to the cells by means of a hemocytometer and flasks were examined under inverted light microscope (Olympus) to count live and dead cells.…”
Section: Methodsmentioning
confidence: 99%
“…SMCs, harvested from the media of rabbit aorta by a collagenase and elastase method as described previously, 10,11 were cultured in Dulbecco's modified Eagle's medium (DMEM, Gibco Laboratories Inc., Grand Island, NY) supplemented with 15% fetal bovine serum (FBS, Gibco Lab. Inc.), 50 IU/mL penicillin, 50 µg/mL streptomycin (Flow Lab., Irvine, Scotland), and 2.5 µg/mL amphotericin B (ICN Biomedicals Inc., Aurora, OH).…”
Section: Methodsmentioning
confidence: 99%